CHARACTERIZING CHICKEN EGGSHELL REINFORCED POLYPROPYLENE (PP) - Sivarao, Subramonian; Azhar Shah, Abu Hassan; Rizal, M S; Ahmad , Kamely; Tajul Ariffin, Abdullah; Taufik, , (International Islamic University Malaysia, 2009)
Chicken eggshell (ES) is an industrial by product containing 95% calcium carbonate and its disposal constitutes a serious environmental hazard. ES contains about 95% calcium carbonate in the form of calcite and 5% organic materials such as type X collagen, sulfated polysaccharides, and other proteins. Although there have been several attempts to use eggshell components for different applications, its chemical composition and availability makes eggshell a potential source of filler for PP composites. In this research work, different proportions of chicken eggshell as bio-filler for polypropylene (PP) composite were compared with different operating temperature by creep test, hardness test and SEM photomicrographs. The eggshell had been prepared by blending and sieving them into granule size of less than 160µm. The granules were then mixed with polypropylene into four weight ratios, 10%, 20%, 30% and 40% respectively using fine extruder, where silane was used as the coupling agent. From the result, it was learnt that, the ES filler had improved Creep Strain and Creep Modulus for the operating temperatures of 34°C and 80°C. Tensile and flexural tests were also performed to study the pattern and behaviour of the chicken egg shell particulated polypropylene. In general, the findings can be concluded that not all ratios of particulation yielded positive as expected, but there were also conditions where virgin polypropylene yields better result depending on the test type and composite matrices.